2005
DOI: 10.1111/j.1746-1049.2005.tb00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Union Effect on the Use of Non-Regular Labor in the Republic of Korea

Abstract: Our paper aims at analyzing the union effect on the externalization of employment relations, focusing on how labor unions affect management's strategic use of non-regular labor within the Korean context of industrial relations. Our study presents several interesting implications. Firstly, the unions' motivator role for managerial use of non-regular labor is more evident than its constrainer role. Secondly, union power exerts a "U-type" impact on the use of indirect non-regular labor, while affecting directly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The differences in the influence of unions are not taken into consideration in those studies. There exist some other studies that examine different approaches by management towards the use of non-regular workers, which are related to union variables, such as the attitude of unions, union–management conflicts and collective bargaining for non-regular workers (Lee et al, 2005; Lee and Lee, 2003). Olsen (2005) found that a company’s use of non-regular workers depends on union attitudes, and that union attitudes in turn depend on a company’s motives for employing non-regular workers.…”
Section: Literature Review Of the Unionization Of Part-time Workersmentioning
confidence: 99%
“…The differences in the influence of unions are not taken into consideration in those studies. There exist some other studies that examine different approaches by management towards the use of non-regular workers, which are related to union variables, such as the attitude of unions, union–management conflicts and collective bargaining for non-regular workers (Lee et al, 2005; Lee and Lee, 2003). Olsen (2005) found that a company’s use of non-regular workers depends on union attitudes, and that union attitudes in turn depend on a company’s motives for employing non-regular workers.…”
Section: Literature Review Of the Unionization Of Part-time Workersmentioning
confidence: 99%